Molecular identification of isolates of Trichoderma spp as biocontroller of Fusarium falciforme, causal agent of root rot of table manioc (Manihot esculenta Crantz) var. rosinha in the State of Alagoas/Brazil (Research, Society and Development, 2022)
Root rot caused by pathogens limits the production of cassava (Manihot esculenta Crantz), a crop of high interest for the Northeast region of Brazil. The difficulty in management has led to the search for alternatives, among which, the biocontrol with Trichoderma spp, has been showing significant results. Due to the importance of the cassava crop and the existing phytosanitary problems, this work aimed to identify, through molecular tools, the isolates of Trichoderma spp. that obtained the best performance in inhibiting the development of F. falciforme. Trichoderma isolates were selected by the method of confrontation and production of metabolites. Subsequently, the DNA was extracted and the sequencing of the ITS region was performed for phylogenetic analysis. Twelve Trichoderma isolates were obtained, among which, five (T5; T6; T10; T13; T15) produced bioactive substances that significantly inhibited the development of F. falciforme. The T5; T6 and T15 were submitted to a phylogenetic study based on the ITS region of the DNA because they presented better results. The results of the phylogenetic analysis based on the gene sequences of the ITS region of the DNA, revealed with 100% reliability that the isolates are of the genus Trichoderma, being T5 of the species T. citrinoviride with 99% of similarity in the sequence; T6 is T. harzianum with 95% and T15 is T. orientale with 95%. The isolates T. citrinoviride and T. orientale are the first reports of these species acting as biocontrollers of phytopathogens in cassava plantation areas in the state of Alagoas.